2012
DOI: 10.1093/humrep/des279
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial gene expression in the early luteal phase is impacted by mode of triggering final oocyte maturation in recFSH stimulated and GnRH antagonist co-treated IVF cycles

Abstract: EudraCT number 2009-009429-26, protocol number 997 (P06034).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Both ploidy and age-related unique changes in human blastocysts microRNA profile have been reported recently [17]. The present hCG data were not adjusted for differences in stimulatory regimens used in the cycles, and hence it cannot be excluded that the observed effect is due to differences in COS which have been shown to influence the gene expression of the endometrium [18,19]. …”
Section: Discussionmentioning
confidence: 90%
“…Both ploidy and age-related unique changes in human blastocysts microRNA profile have been reported recently [17]. The present hCG data were not adjusted for differences in stimulatory regimens used in the cycles, and hence it cannot be excluded that the observed effect is due to differences in COS which have been shown to influence the gene expression of the endometrium [18,19]. …”
Section: Discussionmentioning
confidence: 90%
“…There is some evidence in both mice and humans to support differential endometrial gene expression based on the stimulation protocol used for superovulation, and this may influence placentation and growth (52, 53). Although changes in stimulation protocols may favorably alter endometrial gene expression, there is insufficient evidence currently to recommend an optimal regimen to maximize favorable endometrial gene expression profiles.…”
Section: Effects On the Endometriummentioning
confidence: 99%
“…Clinical studies have confirmed that elevated P before hCG administration is associated with decreased pregnancy rates in IVF, suggesting that an elevated P level does, in fact, shift the window of receptivity and reduce normal embryo implantation (38, 42). Supplementing P during the luteal phase alters endometrial gene expression, and luteal phase supplementation may be able to overcome some of the changes in endometrial receptivity induced by other aspects of superovulation (53, 78, 79). Although supplemental P is given to patients during both fresh and frozen embryo transfer cycles, the timing of P exposure differs in a fresh cycle, because the premature elevations in P often seen during stimulation in a fresh cycle do not occur in a frozen cycle.…”
Section: Potential Mediators Of These Effectsmentioning
confidence: 99%
“…A premature rise (>1.5 ng/mL) in progesterone may occur in spite of using GnRH agonist or antagonist for pituitary suppression during COS and is often associated with increased ovarian response (i.e., high estrogen levels and follicle numbers). Although the exact cause-andeffect mechanisms of a premature progesterone rise is not fully understood, it has been suggested to involve the advancement of endometrial development and in altered endometrial gene expression [7][8][9][10]. In some studies, cycles with elevated progesterone levels before ovulation induction have been associated with reduced pregnancy and live birth outcomes, suggestive of reduced endometrial receptivity and placentation [3,5].…”
Section: Introductionmentioning
confidence: 99%